Cultural and pathogenic variability in Bipoiaris sorokiniana causing spot blotch of wheat in North India - and RAMJI SINGH, AMIT CHAUHAN*, R.V. SINGH (Indian Phytopathology, 2007)
Variability among 6 isolates of Bipolaris sorokiniana was studied. Maximum colony diameter and sporulation was observed in Faizabad isolate (BS-F-5) and minimum in Delhi isolate (BS-D-2). The colony shape of different isolates varied from irregular to smooth and colour varied from gray with whitish dots, olivaceous, brown to dark black. The colony texture varied from fluffy, fluffy cottony, to appressed and semi appressed. Maximum average length and width of conidiophore were observed in Faizabad (BS-F-5) and Kanpur (BS-K4) isolates, respectively, while minimum average length and width were observed in DWR (BS-DWR-K-1) and Delhi (BS-D-2) isolates, respectively. The colour of conidiophore varied from light brown to light olivaceous. Maximum average length and width of conidia were observed in Varanasi (BS-V-6) isolate, while minimum length and width were observed in Kanpur (BS-K-4) and Faizabad (BS-F-5) isolates, respectively. Maximum number of septa in conidiophore and conidia were observed in Faizabad (BS-F-5) isolate, while minimum in Kanpur (BS-K-4) and Delhi (BS-D-2) isolates, respectively. As far as pathogenic variability is concerned, Faizabad (BS-F-5) and Pusa (BS-P-3) isolates were highly virulent whereas Delhi isolate (BS-D-2) was found to be comparatively less virulent against seven different wheat genotypes tested in the present studies. All seven genotypes expressed resistant to highly susceptible reaction against six isolates of B. sorokiniana.